Intraoperative local infiltration anesthesia effect on post-operative pain after total knee replacement - Jbarat, Ashraf M.; Obeidat, Mohammad M.; Alsarhan, Hamed A.; Al-Oun, Mohammad H.; Al-Tarawni, Laith K. (International Journal of Research in Orthopaedics, 2023)
Background: Pain following TKA renders rehabilitation difficult. Local infiltration anesthesia (LIA) could significantly decrease post-operative pain. Aim was to assess the effect of peri-articular intraoperative LIA during primary TKA on post-operative pain. Methods: This prospective, randomized and double-blind study included 150 patients, aged 65-74 years, of both sexes with stage 4 knee osteoarthritis who were assigned for primary TKA at Queen Alia Military hospital, Amman-Jordan, during the period May 2022–December 2022. Patients were divided into two groups. LIA group (GI, n=75) received a single peri-articular LIA during surgery. The cocktail comprised 75 mg diclofenac sodium, 100 mg bupivacaine, and 0.5 mg adrenaline. The cocktail was diluted in 100 ml of normal saline and split into two syringes, 50 ml each. Patients in control group (GII, n=75) received only 100 ml of normal saline. When patients had pain postoperatively, 1 mg morphine was given intravenously at 15-minute intervals. Primary outcomes were verbal analog scale (VAS) pain score from day 1 to 6 after surgery and overall morphine administration. Results: On day 1 after surgery, the average VAS was 4.19 in the LIA group vs. 6.08 in group II (p<0.002), while it was 4.01 versus 4.78 (p>0.05) on day 6. Overall morphine requirement and pain scores from day 1 to day 6 after surgery were less in the LIA group than in the other group, 13.06 mg versus 20.75 mg (p<0.004). Conclusions: Peri-articular LIA during TKA significantly improve post-operative pain and decreases morphine use.